Kulturális tőke és társadalmi mobilitás (Szociológiai Szemle, 2024)
The paper studies the effects of cultural capital, acquired in the parental home, on social - school and occupational - mobility. According to the hypothesis, supported by regression equations, cultural capital is able to substitute for the limitations of other resources and it is able to promote the individual, supplied abundantly by cultural capital, into a more favourable status than the social position occupied by the parents. Whereas the relatively limited cultural capital, inherited by an individual, may set him or her out downwards in the social hierarchy. After the theoretical unfolding of the hypothesis it is shown that social mobility, guided by cultural capital, does really exist in the twentieth-century Hungary, but it is also revealed that its role is decreasing. However, marked differences can be found not only among the various cohorts in the operation of the mechanism, but also between men and women. If the sample is further broken up, it is found that the chances of mobility of girls are far more vigorously influenced by cultural capital than those of boys.